Reducing Drug Trafficking Revenues and Violence in Mexico Would Legalizing Marijuana in California Help? - Kilmer, Beau (RAND Corporation, 2010)
U.S. demand for illicit drugs creates markets for Mexican drug- trafficking organizations (DTOs) and helps foster violence in Mexico. This paper examines how marijuana legalization in California might influence DTO revenues and the violence in Mexico.